Fostering mathematical creativity and autonomy through a STEM-based digital learning space - Yulianto, Dwi; Juniawan, Egi Adha (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Although STEM education emphasizes the integration of science, technology, engineering, and mathematics to foster 21st-century competencies, in Indonesian secondary schools STEM subjects are still commonly taught in isolation, while digital learning remains limited to passive presentation tools with little personalization. This gap highlights the need for innovative designs that connect STEM domains and foster higher-order mathematical skills. To address this, the present study develops and evaluates a STEM-Based Digital Learning Space (DLS) integrating a Personal Learning Environment (PLE) and a Personal Teaching Environment (PTE), aimed at enhancing junior high school students’ creative mathematical thinking and autonomous learning in probability. Using the 4D model (Define, Design, Develop, and Disseminate), the DLS was validated by experts (Aiken’s V ≥ 0.80) and tested through multi-stage field trials: a pilot (n = 7), an expanded trial (n = 60, two schools), and a large-scale implementation (n = 120, four schools). Results confirmed high feasibility (Mean = 95.07%, SD = 1.2) and practicality (Mean = 89.38%, SD = 2.1). Effectiveness testing demonstrated significant gains in creative mathematical thinking (N-Gain = 0.554, moderate effect) and strengthened autonomous learning, supported by significant interaction effects (F = 4.62, p < .05). Specific features yielded measurable outcomes: simulations enhanced fluency and flexibility, adaptive quizzes supported metacognitive regulation, digital worksheets improved originality, and collaborative forums fostered responsibility. Overall, the DLS proved effective even in low-resource contexts and scalable through teacher training, offering evidence-based guidance for advancing digital literacy and supporting the Merdeka Belajar policy.